Cooperative Learning Teams Games Tournament (TGT) with Content Differentiation Approach: An Effort to Improve Student Learning Outcomes in Whole Number Topics - Isaloka, Ilo; Wiryanto, Wiryanto; Mufidah, Lailatul (JagoMIPA: Jurnal Pendidikan Matematika dan IPA, 2024)
Students often perceive mathematics as difficult and abstract, negatively affecting their interest and motivation to learn. The Teams Games Tournament (TGT) model was chosen because it incorporates healthy competition into the learning process, encouraging students to engage more actively. The main objective of this study is to improve the learning outcomes of fourth-grade students in a whole number topics by applying the Cooperative Learning Teams Games Tournament (TGT) model with a content differentiation approach. This study used Classroom Action Research (CAR) carried out in two cycles. Each cycle consists of four stages: planning, acting, observing, and reflecting. The research subjects were 27 fourth-grade students at SDN Sidosermo I Surabaya in the 2023/2024 academic year. Learning outcome data were collected through pre-tests and post-tests to assess students’ understanding before and after the intervention. The data were analyzed using descriptive analysis methods to describe the average scores and the percentage of student mastery in each cycle. Based on the pre-test results, the average student score was 61.48, with a mastery rate of 40.74%, which is below the minimum passing criterion (KKM) of 75. After the intervention in Cycle 1, the average score increased to 80.85, with a mastery rate of 52%. In Cycle 2, following strategy improvements, the average score reached 86.78, with 85% mastery. These results indicate that the TGT model with a content differentiation approach is effective in improving students' understanding and learning outcomes, surpassing the 80% mastery criterion.